Stroke 20 20: Implementation goals for intravenous thrombolysis. (June 2021) - Mikulik, Robert; Bar, Michal; Cernik, David; Herzig, Roman; Jura, Rene; Jurak, Lubomir; Neumann, Jiri; Sanak, Daniel; Ostry, Svatopluk; Sevcik, Petr; Skoda, Ondrej; Skoloudik, David; et al.
Introduction: Knowledge of the implementation gap would facilitate the use of intravenous thrombolysis in stroke, which is still low in many countries. The study was conducted to identify national implementation targets for the utilisation and logistics of intravenous thrombolysis. Material and Method: Multicomponent interventions by stakeholders in health care to optimise prehospital and hospital management with the goal of fast and accessible intravenous thrombolysis for every candidate. Implementation results were documented from prospectively collected cases in all 45 stroke centres nationally. The thrombolytic rate was calculated from the total number of all ischemic strokes in the population of the Czech Republic since 2004. Results: Thrombolytic rates of 1.3 (95%CI 1.1 to 1.4), 5.4 (95%CI 5.1 to 5.7), 13.6 (95%CI 13.1 to 14.0), 23.3 (95%CI 22.8 to 23.9), and 23.5% (95%CI 23.0 to 24.1%) were achieved in 2005, 2009, 2014, 2017, and 2018, respectively. National median door-to-needle times were 60–70 minutes before 2012 and then decreased progressively every year to 25 minutes (IQR 17 to 36) in 2018. In 2018, 33% of both university and non-university hospitals achieved median door-to-needle time ≤20 minutes. In 2018, door-to-needle times ≤20, ≤45, and ≤60 minutes were achieved in 39, 85, and 93% of patients. Discussion: Thrombolysis can be provided to ≥ 20% of all ischemic strokes nationwide and it is realistic to achieve median door-to-needle time 20 minutes. Conclusion: Stroke 20–20 could serve as national implementation target for intravenous thrombolysis and country specific implementation policies should be applied to achieve such target.